A General Strategy Assisted with Dual Reductants and Dual Protecting Agents for Preparing Pt‐Based Alloys with High‐Index Facets and Excellent Electrocatalytic Performance. Issue 46 (16th October 2017) - Luan, Chenglong; Zhou, Qing‐Xiang; Wang, Yao; Xiao, Yun; Dai, Xiaoping; Huang, Xing‐Liang; Zhang, Xin
Abstract: Synthesizing noble metallic nanoparticles (NPs) enclosed by high‐index facets (HIFs) is challenged as it involves the tuning of growth kinetics, the selective adsorption of certain chemical species, and the epitaxial growth from HIF enclosed seeds. Herein, a simple and general strategy is reported by using dual reduction agents and dual capping agents to prepare Pt‐based alloy NPs with HIFs, in which both glycine and poly(vinylpyrrolidone) serve as the reductants and capping agents. Due to the facilely tunable growth/nucleation rates and protecting abilities of the reductants and capping agents, Pt concave nanocube (CNC), binary Pt–Ni CNC, ternary Pt–Mn–Cu CNC, and Pt–Mn–Cu ramiform polyhedron alloy NPs terminated by HIFs as well as other NPs with well‐defined morphologies such as Pt–Mn–Cu nanocube and Pt–Mn–Cu nanoflower are obtained with this approach. Owing to the high density of low‐coordinated Pt sites (HIF structure) and the unique electronic effect of Pt–Mn–Cu ternary alloys, the as‐prepared Pt–Mn–Cu NPs show enhanced catalytic activity toward methanol and formic acid electro‐oxidation reactions with excellent stability. This work provides a promising methodology for designing and fabricating Pt‐based alloy NPs as efficient fuel cell catalyst. Abstract : Novel platinum based alloy nanoparticles enclosed by high‐index facets are synthesized to efficiently catalyze methanol and formic acid electro‐oxidation reactions by rationally employing poly(vinylpyrrolidone) and glycine as dual reductants and dual protecting agents.